From Field to Fermentation: Optimizing Peanut Vine Nutrients Through Advanced Harvest and Silage Practices - Kai Li; Chunran Teng; Junhong Wang; Yuxiang Liang; Xiaokang Jing; Ruqing Zhong; Liang Chen; Hongfu Zhang (Agronomy, 2025)
The study’s objectives were three-fold. Firstly, the impacts of three advanced harvest times (10 days, 5 days, 0 days) on the nutrient composition of peanut vine (PV) were investigated to determine the optimal harvesting time for peanut vine; secondly, the chemical composition and fermentation characteristics of silage produced by combining peanut vine with either wheat bran (PV-WB silage) or corn meal (PV-CM silage) with adding different inoculants (named as TTX, DBN, and JNK) were evaluated; finally, the post-ensilage microbial community was analyzed to assess the effects of inoculants and silage substrates on the bacterial and fungal communities, as well as their interactions. The results indicated that harvesting peanut vine 5 days early significantly enhanced the retention of crude protein and reduced the content of acid detergent fiber and acid detergent lignin compared to harvesting at 0 days (p < 0.05). PV-WB silage exhibited higher crude protein content than PV-CM silage, irrespective of the inoculant used (p < 0.05). The application of the TTX inoculant notably reduced the acid detergent lignin content and enhanced the potential biodegradation, while also increasing the concentrations of acetic acid and lactic acid (p < 0.05). The bacterial community was predominantly composed of the genera Lactobacillus, Pediococcus, and Weissella; however, a greater abundance of Enterobacter and Enterococcus was obtained in the control (CON) treatment. The use of the JNK inoculant resulted in a Saccharomyces abundance exceeding 89%, which led to elevated levels of ammonia-N and higher pH values. In summary, the advanced 5 days to harvest peanut vines retained more crude protein content and decreased the acid detergent fiber and acid detergent lignin content. Fresh peanut vines co-silage with WB including TTX inoculant improved the peanut value nutrient preservation and fermentation parameters.